Laudato Si' - socioeconomic relevance for a dynamic, shifting, and challenging future - Pavlić, Richard (Array, 2021)
The paper deals with the relevance of Laudato Si", five years after its publication. Given the Covid-19 crisis, which triggered the new economic crisis in the world, we believe that Laudato Si" is more relevant in 2020 than it was in 2015. The paper analyzes three socioeconomic segments of Laudato Si" to present its relevance today: mankind and our relationship with others, God and environment, the new economic crisis, and needed global action to comprehend and overcome the Covid-19 crisis. The processes and dangers of five years ago have not disappeared, they have only changed form. Thus, Laudato Si" is not only relevant but can be used as a socioeconomic reconstruction program for Covid-19 aftermaths.